Odpowiedź:
1.
a. [tex]1\frac{6}{11}+\frac{8}{11}=2\frac{3}{11}[/tex]
b. [tex]2\frac{2}{5}+ 1\frac{1}{6} = 3\frac{17}{30}[/tex]
c. [tex]1\frac{3}{11}-\frac{9}{11} = \frac{5}{11}[/tex]
d. [tex]6\frac{8}{15 } - 3\frac{2}{15} = 3\frac{2}{15}[/tex]
2.
a.[tex]15 * 4\frac{2}{3} = 70[/tex]
b. [tex]1 \frac{1}{3} * 3 \frac{3}{4} = 5[/tex]
c. [tex]3\frac{3}{4}:12 = \frac{5}{16}[/tex]
d. [tex]7\frac{1}{3} : 1 \frac{4}{7} =\frac{14}{3} = 4\frac{2}{3}[/tex]
3. [tex](\frac{4}{9} - \frac{1}{4}) : (3+\frac{1}{2} )= -\frac{5}{36} :\frac{7}{2} = -\frac{5}{36} * \frac{2}{7}= -\frac{5}{18} * \frac{1}{7} = -\frac{5}{126}[/tex]
Szczegółowe wyjaśnienie: